The Fabric of Basketry: Initial Archaeological Study of the Grass Artifacts Assemblage from the Nunalleq Site, Southwest Alaska - Masson-MacLean, Julie; Masson-MacLean, Edouard; Knecht, Rick (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2019)
More than two thousand archaeological grass artifacts dating from the fifteenth to the seventeenth century have been recovered from Nunalleq (GDN-248), an archaeological site located near the village of Quinhagak, southwest Alaska, in eight seasons of fieldwork at the site. This growing collection of basketry and cordage provides unprecedented insights on the use of grass artifacts in precontact Yup’ik households. Permafrost soils have preserved this assemblage astonishingly well, with objects made from grass blades and roots. Here we present the results of a preliminary study of these rarely encountered artifacts, based on the data recorded in the course of conservation work.